2019
DOI: 10.1371/journal.ppat.1008249
|View full text |Cite
|
Sign up to set email alerts
|

Cross-talk between microglia and neurons regulates HIV latency

Abstract: Despite effective antiretroviral therapy (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
90
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(90 citation statements)
references
References 163 publications
(127 reference statements)
0
90
0
Order By: Relevance
“…Although macrophages have been postulated to harbor HIV-1 as transcriptionally silent provirus or unintegrated DNA (see the review in [38]), frequency and mode of HIV-1 latency in tissue-resident macrophages in patients on therapy are largely unknown. HIV latency has been hypothesized to be reactivated by multiple mechanisms such as co-infections and cytokines [39,40]. Whether latently infected microglia in HIV + individuals are reactivated with such stimuli and to what extent HIV production from microglia can contribute to systemic viremia remain to be determined.…”
Section: Hiv Persistence In Tissue-resident Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Although macrophages have been postulated to harbor HIV-1 as transcriptionally silent provirus or unintegrated DNA (see the review in [38]), frequency and mode of HIV-1 latency in tissue-resident macrophages in patients on therapy are largely unknown. HIV latency has been hypothesized to be reactivated by multiple mechanisms such as co-infections and cytokines [39,40]. Whether latently infected microglia in HIV + individuals are reactivated with such stimuli and to what extent HIV production from microglia can contribute to systemic viremia remain to be determined.…”
Section: Hiv Persistence In Tissue-resident Macrophagesmentioning
confidence: 99%
“…Additional advantages include the feasibility of establishing iPSC lines from patients with diverse genetic backgrounds, such as those with microglia-associated neurodegenerative diseases [81] or those with higher CNS HIV reservoirs, which might reveal pathways that could be harnessed to suppress disease states. A recent study has used commercially available iPSC-derived microglia and demonstrated that neuronal status (healthy or damaged) affects HIV replication in microglia, indicating interplay between microglia and neurons [40]. Further studies are warranted to use microglia and neurons from the same iPSC line and to include other CNS-resident cells such as astrocytes to form self-organizing three-dimensional organoid cell cultures to recapitulate cell-to-cell interactions and model brain structures in HIV-infected states.…”
Section: Pro-inflammatory Responses In Tissue (Cns)-resident Macrophagesmentioning
confidence: 99%
“…Microglia are the resident tissue macrophages of the brain, derived from yolk sac progenitors, and are known to interact extensively with surrounding brain parenchymal cells including neurons and astrocytes, where they perform many essential functions [22][23][24]. In HIV-1 infection, microglia may contribute to CNS dysfunction and the development of HAND through excessive or unchecked activation [25] and may also serve as a viral reservoir [19,26,27]. Understanding HIV-1 interactions with microglia will likely be important in developing a comprehensive strategy to prevent or treat HAND.…”
Section: Introductionmentioning
confidence: 99%
“…This cell line and subsequent derivatives have also been termed CHME-5 [30] and C13-NJ [31]. More recently, Alvarez-Carbonell and coworkers [32] transformed cells from adult brain tissue with lentiviral vectors expressing SV40 T antigen or a combination of SV40 T antigen and hTERT [26]. They demonstrated that these immortalized cells have microglia-like morphology and express key microglial surface markers, and utilized them for generating latently infected clones that reactive HIV in response to inflammatory signals [32].…”
Section: Introductionmentioning
confidence: 99%
“…This cell line and subsequent derivatives have also been termed CHME-5 [30] and C13-NJ [31]. More recently, Alvarez-Carbonell and coworkers [32] transformed cells from adult brain tissue with lentiviral vectors expressing SV40 T antigen or a combination of SV40 T antigen and hTERT [26]. They demonstrated that these immortalized cells have microglia-like morphology and express key microglial surface markers, and utilized them for generating latently infected clones that reactivate HIV in response to in ammatory signals [32].…”
mentioning
confidence: 99%